PENERAPAN PENDIDIKAN AGAMA KRISTEN DALAM PENGEMBANGAN KARAKTER PENGAMPUNAN DI SEKOLAH DASAR TEOLOGI KRISTEN TUNAS PERTIWI BOGOR - Gea, Lestariani; Odoh, Obden Sumero (JURNAL KADESI, 2024)
Christian religious education basically aims to gradually direct students to understand the events recorded in the Bible and the teachings conveyed through the Bible. The primary goal is to guide students in the Bible to guide all aspects of their lives toward salvation. Apart from that, Christian religious education also aims to encourage students to apply Biblical principles in forming a strong and convincing Christian character, as well as recognizing that the truth and principles of faith can be a guide in overcoming moral, social and political problems in the world. This world.The aim of implementing Christian religious education in developing the character of forgiveness is a way to resolve conflicts between the two parties. The character of forgiveness is not just to forget old or recent events. Forgiveness functions to break the chain of hostility, bitter memories that will always be remembered. However, when someone has forgiven the offender's mistakes, there is no longer any pain in the heart even if they still remember the name or memory of the person concerned. Forgiveness is one of the characteristics of Jesus Christ who was willing to die on the cross to forgive humanity's mistakes. The character of forgiveness must be the character of students at SDTK Tunas Pertiwi even though it is difficult to implement. God's Word reminds someone to forgive if someone else makes a mistake to him (Matt. 6:14). The result of the analysis of the character of forgiveness is someone who has a big heart and is still willing to forgive. This research was carried out using quatitative methods.